Flow cytometric analysis of the cellular DNA content of Salmonella typhimurium and Alteromonas haloplanktis during starvation and recovery in seawater. - Lebaron, P (1994)
Flow cytometry was used to investigate the heterogeneity of the DNA content of Salmonella typhimurium and Alteromonas haloplanktis cells that were starved and allowed to recover in seawater. Hoechst 33342 (bisbenzimide) was used as a DNA-specific dye to discriminate between DNA subpopulations. The DNA contents of both strains were heterogeneous during starvation. S. typhimurium cells contained one or two genomes, and A. haloplanktis cells contained up to six genomes. S. typhimurium genomes were fully replicated at the onset of starvation. Each replication cycle was completed in the early stage of starvation for A. haloplanktis by stopping cells in the partition step of the cell cycle prior to division. Multigenomic marine cells can undergo rapid cell division without DNA synthesis upon recovery, resulting in large fluctuations in the DNA contents of individual cells. In contrast, the heterogeneity of the DNA distribution of S. typhimurium cells was preserved during recovery. The fluctuations in the DNA fluorescence of this strain seem to be due to topological changes in DNA. Flow cytometry may provide a new approach to understanding dynamic and physiological changes in bacteria by detecting cellular heterogeneity in response to different growth conditions.